ANALISIS KONTRASTIF KALIMAT IMPERATIF BAHASA INDONESIA DAN BAHASA INGGRIS - Nasution, FAUZIA FAHMI Y ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research discusses Indonesian and English imperative sentences, and also the differences as well as the similarities between them. Futhermore, the aims of the research are (a) to describe the rules and forms of Indonesian imperative sentences, (b) to describe the rules and forms of English imperative sentences, and (c) to find out and describe the similarities and differences between Indonesian and English imperative sentences. This research is contrastive in nature with aspect of emphasizing the syntax. In collecting the data, the researcher uses observation method and recording technique. The English imperative sentences are collected from the English grammar books